Visual statistical learning in deaf and hearing infants and toddlers. (7th May 2022) - Monroy, Claire; Yu, Chen; Houston, Derek
Abstract: Congenital hearing loss offers a unique opportunity to examine the role of sound in cognitive, social, and linguistic development. Children with hearing loss demonstrate atypical performance across a range of general cognitive skills. For instance, research has shown that deaf school‐age children underperform on visual statistical learning (VSL) tasks. However, the evidence for these deficits has been challenged, with mixed findings emerging in recent years. Here, we used a novel approach to examine VSL in the action domain early in development. We compared learning between deaf and hearing infants, prior to cochlear implantation (pre‐CI), and a group of toddlers post implantation (post‐CI). Findings revealed a significant difference between deaf and hearing infants pre‐CI, with evidence for learning only in the hearing infants. However, there were no significant group differences between deaf and hearing toddlers post‐CI, with both groups demonstrating learning. Further, VSL performance was positively correlated with language scores for the deaf toddlers, adding to the body of evidence suggesting that statistical learning is associated with language abilities. We discuss these findings in the context of previous evidence for group differences in VSL skills, and the role that auditory experiences play in infant cognitive development.